2022
DOI: 10.1007/s10238-022-00900-6
|View full text |Cite
|
Sign up to set email alerts
|

High plasma EBV-DNA load and positive EBER status associated with viral recurrence and persistent infection in early treatment of lymphoma

Abstract: The relationship between plasma EBV-DNA load (PEDL) and Epstein-Barr virus (EBV)-encoded small RNA (EBER) during early treatment of lymphoma remains unclear. We explored discrepancies in PEDL and variables associated with EBER, and evaluated the consistency between EBER and qualitative analysis of PEDL (qPEDL). Serial measurements of PEDL were performed to determine the dynamic changes of PEDL in early treatment of lymphoma. As a result, the median PEDL of NHL-NKT was higher than that of NHL-B, the median PEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Jiang et al reported higher levels of β2-microglobulin in lymphoma-associated HLH compared to benign disease-associated HLH, consistent with our study [30]. EBER positivity has been reported to correlate with a higher plasma EBV-DNA load, both indicators of a more severe condition and a poorer prognosis [31,32]. In this study, EBV-positive LA-HLH patients showed higher plasma EBV-DNA levels and a greater proportion of EBER positivity, which may suggest a prolonged and more severe EBV infection in these individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Jiang et al reported higher levels of β2-microglobulin in lymphoma-associated HLH compared to benign disease-associated HLH, consistent with our study [30]. EBER positivity has been reported to correlate with a higher plasma EBV-DNA load, both indicators of a more severe condition and a poorer prognosis [31,32]. In this study, EBV-positive LA-HLH patients showed higher plasma EBV-DNA levels and a greater proportion of EBER positivity, which may suggest a prolonged and more severe EBV infection in these individuals.…”
Section: Discussionsupporting
confidence: 91%